Analisa Pengaruh Batuan Asal Terhadap Profil Nikel Laterit Menggunakan Analisis XRF Dan Petrografi Di Daearah Kolaka Utara - Husain, Jamal Rauf; Harwan, Harwan; Mustakim, Mustakim (CV Insight Publisher, 2023)
Nickel is one of the metals needed by humans. In general, nickel can be formed primarily or secondarily, known as nickel laterite. Nickel deposits in Indonesia are only found in the form of nickel laterite. The parent rock of nickel laterite deposits is ultrabasic rock, especially from the types of harzburgite, dunite, and other peridotites. The data collection technique used is to take data related to the research, both primary and secondary data. Primary data includes outcrop data (megascopic description) at the research location, exploration drill data to determine the thickness of the nickel laterite layer and the content of its elements and rock sample data for petrographic thin section analysis. Sampling was carried out in block A. While secondary data includes data on the general condition of the company, and a map of the research location. 1. The original rock analyzed petrographically is serpentinezed harzburgite. The minerals contained are orthopyroxene, olivine, clinopyroxene, and opaque minerals. The weathering level of the nickel laterite profile in the limonite zone is higher than the saprolite zone because in the saprolite zone most of the rocks are small in size and the original rocks affect the nickel laterite profile that is formed, but are still supported by other factors, namely topography, climate, geological structure, vegetation and time.